Response to: Biomedical Solid Waste Management System in Jimma Medical Center, Jimma Town, South Western Ethiopia [Letter] - Fikri E (Dove Medical Press, 2023)
Elanda Fikri1,2 1Department of Environmental Health, Poltekkes Kemenkes Bandung, Bandung, Jawa Barat, Indonesia; 2Center of Excellence on Utilization of Local Material for Health Improvement, Bandung Health Polytechnic, Bandung, IndonesiaCorrespondence: Elanda Fikri, Department of Environmental Health, Poltekkes Kemenkes Bandung, Jl.Pajajaran 56, Bandung, Jawa Barat, Indonesia, Email elandafikri@yahoo.com